Martin Versfeld A South African Philosopher in Dark Times - Wolff, Ernst (Leuven University Press, 2021)
"Martin Versfeld (1909-1995) is one of South Africa's greatest philosophers, appreciated by academics and activists, poets and the broader public. His masterful prose spans the tension between disquiet and joy. Detractor of the violent trends of modernity, a critic of apartheid from the first hour, he was among the first philosophers of ecology. At the same time he celebrated the generosity of the world and advocated an ethics of simplicity, drawing on mediaeval theology and Eastern wisdom. His philosophy offered food for thought in dark times of the 20th century, as it still does for us in the 21st century. This first book-length study on Versfeld is an invitation to think with him on justice and exploitation, cultural difference and human nature, religion and the environment, time and connectedness."